The mechanism for applying the results of the EAEA EA for evaluating the effectiveness of the organization of the educational process (Journal of Educational Sciences, 2018)
This article outlines the results of theexternal assesment of educational achievements (EAEA) in 2017in higher education institutions (HEI). According to the results of the EAEA in 2017, comparative figuresof students were presented on the diagrams and tables of students on the state educational grant and ona fee basis. The indicators of the results of the EAEA -2017 are presented in the form of a traditional anda credit rating system. In the direction of «Natural Sciences» a comparative analysis was carried out in thecontext of the status of higher education institutions, in the context of specialties and in the language ofinstruction. The site of the National Testing Center www.testcenter.kzKey words: external assesment of educational achievements, analysis, rating.